2018
DOI: 10.3233/jad-170811
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory Levels of Toxic Metals (Aluminum, Cadmium, Mercury, Lead) in Patients with Alzheimer’s Disease: A Quantitative Meta-Analysis and Systematic Review

Abstract: Compared to controls, circulatory levels of aluminum, mercury, and cadmium are significantly higher but the levels of lead were reduced in AD patients. These findings suggest that elevated aluminum, mercury, and cadmium in the circulation, especially in serum may play a role in the progression of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 62 publications
(66 reference statements)
2
42
0
Order By: Relevance
“…Alzheimer's disease (AD) is the leading cause of dementia worldwide, and AD patients and their families urgently require novel therapeutics to prevent and slow the progression of this devastating disorder. Hallmarks of AD include amyloid-␤ (A␤) peptide secretion and deposition into neuritic plaques, tau protein hyperphosphorylation and neurofibrillary tangle formation, metal ion dyshomeostasis [1][2][3][4][5][6][7][8][9], oxidative stress and lipid, nucleic acid, and protein damage [10][11][12][13], abortive cell cycle reentry [14][15][16][17][18][19][20][21][22][23][24][25][26], neuroinflammation and microbial dysbiosis [27][28][29][30][31][32][33], insulin resistance [34,35], cerebrovascular dysfunction [36][37][38], synaptic dysfunction [39,40], neuronal loss, endoplasmic reticulum stress [41][42][43][44], and mitochondrial dysfunction [...…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is the leading cause of dementia worldwide, and AD patients and their families urgently require novel therapeutics to prevent and slow the progression of this devastating disorder. Hallmarks of AD include amyloid-␤ (A␤) peptide secretion and deposition into neuritic plaques, tau protein hyperphosphorylation and neurofibrillary tangle formation, metal ion dyshomeostasis [1][2][3][4][5][6][7][8][9], oxidative stress and lipid, nucleic acid, and protein damage [10][11][12][13], abortive cell cycle reentry [14][15][16][17][18][19][20][21][22][23][24][25][26], neuroinflammation and microbial dysbiosis [27][28][29][30][31][32][33], insulin resistance [34,35], cerebrovascular dysfunction [36][37][38], synaptic dysfunction [39,40], neuronal loss, endoplasmic reticulum stress [41][42][43][44], and mitochondrial dysfunction [...…”
Section: Introductionmentioning
confidence: 99%
“…Human epidemiological studies have showed that circulating levels of certain heavy metals are higher in patients with Alzheimer's disease than in control patients (Fathabadi et al 2018;Xu et al 2018). This suggests a potential role of heavy metals in Alzheimer's disease, but it is not yet clear whether they interfere in the development or the progression of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Five fountains have high levels of Al that exceed the maximum allowable limits (200 µg/L) in the international standards for drinking water quality. There are studies reporting the neurotoxic effect of aluminium production, including high Al levels in the pathophysiology of Alzheimer's disease and it is defined as Group‐I carcinogenic by the IARC (; Marques et al ., ; Xu et al ., ).…”
Section: Resultsmentioning
confidence: 99%